2016
DOI: 10.1007/s10493-016-0096-4
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria of the genera Ehrlichia and Rickettsia in ticks of the family Ixodidae with medical importance in Argentina

Abstract: The aim of this study was to get an overview about the occurrence of bacteria from the genus Ehrlichia and Rickettsia in ixodid ticks with medical importance in Argentina. Therefore, in 2013 and 2014, free-living ticks were collected in different provinces of northern Argentina. These ticks were determined as Amblyomma sculptum, Amblyomma neumanni, Amblyomma parvum, Amblyomma triste, Amblyomma ovale, Amblyomma tonelliae and Haemaphysalis juxtakochi. All samples were tested to determine the infection with Ehrli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 50 publications
0
3
0
1
Order By: Relevance
“…The first is associated to propagation of ticks in a new territory through movement of domestic animals. At the site where A. sculptum was collected, water buffalos were introduced more than ten years ago from the Formosa province, where A. sculptum is established (Ivancovich and Luciani, 1992;Sebastian et al, 2017;this work). It is possible that water buffalos translocated from Formosa have carried ticks to Corrientes Province, and A. sculptum has found a new system that is ecologically suitable for its development.…”
Section: Discussionmentioning
confidence: 99%
“…The first is associated to propagation of ticks in a new territory through movement of domestic animals. At the site where A. sculptum was collected, water buffalos were introduced more than ten years ago from the Formosa province, where A. sculptum is established (Ivancovich and Luciani, 1992;Sebastian et al, 2017;this work). It is possible that water buffalos translocated from Formosa have carried ticks to Corrientes Province, and A. sculptum has found a new system that is ecologically suitable for its development.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the PCR assay amplifying the ompA gene that is specific for SFGR resulted negative in this study. However, previous studies have shown [ 24 , 25 ] that the applied PCR assay in this study is not appropriate for the detection of the ompA gene of Ca. R. andeanae and therefore must be replaced by another assay described by Ermeeva et al [ 26 ] in future studies.…”
Section: Resultsmentioning
confidence: 83%
“…R. andeanae in A. maculatum from Peru. Further, this rickettsial agent could be detected in A. parvum from Argentina and Brazil [ 24 , 25 , 28 ] and A. tigrinum from Argentina and Chile [ 29 , 30 ]. DNA of Ca .…”
Section: Resultsmentioning
confidence: 99%
“…En Sudamérica, la enfermedad rickettsial mayormente distribuida es la Fiebre de las Montañas Rocosas, una enfermedad mortal cuando no se instaura un tratamiento antibiótico adecuado (Labruna et al, 2011). Esta infección es provocada por Rickettsia rickettsii la cual es transmitida por la picadura de garrapatas del complejo Amblyomma cajennense, Amblyomma aureolatum y Rhipicephalus sanguineus sensu lato (Guedes et al, 2005;Labruna et al, 2011Labruna et al, , 2014Venzal & Nava, 2011;Venzal, 2013;Parola et al, 2013;Nava et al, 2017). En Argentina, las Fiebres Manchadas se encuentran distribuidas principalmente en dos regiones con cuadros clínicos diferenciados: el norte del país, donde Rickettsia rickettsii ocasiona la Fiebre Manchada, transmitida por especies de garrapatas del complejo…”
Section: Relación En El Hematocrito Y La Abundancia Parasitariaunclassified